P57 Persistent regional variation in treatment of hypertension. (16th November 2010) - Mindell, J; Shelton, N; Roth, M; Chaudhury, M; Falaschetti, E
Abstract : Objective: To investigate risk factors for treatment for hypertension in people with survey-defined hypertension in England. Design: Cross-sectional health examination surveys. Setting: Three, nationally representative random samples of the general population living in private households in England—the Health Survey for England (HSE) in 2005, 2006, and 2007. Participants: A new, nationally representative sample is selected each year. A random sample of the free-living general population (HSE 2005 (n=5321), 2006 (n=10 213), 2007 (n=4848)) were visited by an interviewer then a nurse; the interview was supplemented by physical measurements using standardised protocols. Blood pressure was measured three times with an Omron HEM207 after a 5-min rest. Mean of second and third readings in participants who had not eaten, drunk alcohol, smoked, or exercised in the preceding 30 min were used. Main Outcome Measures: Hypertension was defined as systolic blood pressure ≥140 mm Hg, diastolic blood pressure ≥90 mm Hg, and/or taking prescribed medication to lower blood pressure. Results: A higher proportion of participants in London than elsewhere in England with survey-defined hypertension were on treatment (2005–2007 average: 61% men, 66% women in London; 43% men, 55% women in England, (p for London vs rest of England <0.001 for each sex). Regression analysis showed this regional effect for odds of treatment persisted after adjustment for demographic, socio-economic, and health behaviours (OR 1.48, 95% CI 1.04 to 2.10, p=0.029) and was strengthened (OR1.87 (1.25 to 2.81), p=0.003) by including self-reported health, long-standing illness, diabetes, and cardiovascular disease in the model. Apart from the regional differences, treatment for hypertension increased with age and was more likely among women (OR 1.59 (1.29 to 1.97), p=0.001); former smokers (OR 1.44 (1.05 to 1.99), p=0.026); and people who were married; were overweight (OR 1.40 (1.03 to 1.89), p=0.033) or obese (OR 1.80 (1.32 to 2.42), p<0.001); reported limiting (OR 2.49 (1.93 to 3.20), p<0.001) or non-limiting (OR 3.25 (2.48 to 4.24), p<0.001) long-term illness; or reported diabetes (OR 2.36 (1.60 to 3.47), p<0.001) or cardiovascular disease (OR 1.54 (1.18 to 22.02), p=0.002). Treatment was 39% and 61% less likely in widowed (p=0.004) and co-habiting participants (p<0.001), respectively, and 40% less likely in binge-drinkers (p=0.014). Conclusion: The proportion of people in London being treated for hypertension is above the national average even after adjustment for sociodemographic and health-related factors. This may be due to greater population mobility in London with more people having new Patient Health checks. Education and financial incentives for improvements in detection, treatment and control of hypertension in primary care in England have been beneficial but remain inadequate.